-2(8x-5)+2x=(x+5)

Simple and best practice solution for -2(8x-5)+2x=(x+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(8x-5)+2x=(x+5) equation:


Simplifying
-2(8x + -5) + 2x = (x + 5)

Reorder the terms:
-2(-5 + 8x) + 2x = (x + 5)
(-5 * -2 + 8x * -2) + 2x = (x + 5)
(10 + -16x) + 2x = (x + 5)

Combine like terms: -16x + 2x = -14x
10 + -14x = (x + 5)

Reorder the terms:
10 + -14x = (5 + x)

Remove parenthesis around (5 + x)
10 + -14x = 5 + x

Solving
10 + -14x = 5 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
10 + -14x + -1x = 5 + x + -1x

Combine like terms: -14x + -1x = -15x
10 + -15x = 5 + x + -1x

Combine like terms: x + -1x = 0
10 + -15x = 5 + 0
10 + -15x = 5

Add '-10' to each side of the equation.
10 + -10 + -15x = 5 + -10

Combine like terms: 10 + -10 = 0
0 + -15x = 5 + -10
-15x = 5 + -10

Combine like terms: 5 + -10 = -5
-15x = -5

Divide each side by '-15'.
x = 0.3333333333

Simplifying
x = 0.3333333333

See similar equations:

| 21a+64=547 | | 3t/4=84 | | 3/4+2y=4y-1/20 | | 6t+9=-8+2(t+5) | | (4x-5)(4x-2)= | | 4x+2(x+13)=10 | | 5x(x-2)+6=0 | | y/9+84=272 | | 4y+6=14 | | 6w-9=-2+2(w+2) | | 12b-8=160 | | x-31/8=71/4 | | 5xy+8xy= | | 5xy-8xy= | | (8x^3-4x^2+7x)-(7x^2+3x+5)= | | 4x+2(x+3)=10 | | n/4-32=26 | | -6=2(8-k) | | 7-6u=5u+35 | | 3e(x+1)-5=7 | | 4x^2+x^2=54+6x | | 6x-45=9x-15 | | -6-7(6-5x)=-153 | | (X^2-9X+18)/(X-6) | | -140-8x=9x+24 | | 26x^2-56x=0 | | 6(11-s)=60 | | 4y+7y+11=0 | | (8x+8)-(7x^2+5x+6)= | | 5b-2=4+3(b-9) | | x^2-y^2=49 | | 4y-4=-8 |

Equations solver categories